Hydrogen production from reforming of biogas: review of technological advances and an Indian perspective - Nahar, G.; Mote, D.; V. Dupont (Renewable and Sustainable Energy Reviews, 2017)
This paper examines the benefits and potential of biogas generation and uses in India, with focus on advances made in hydrogen production by catalytic reforming technologies with steam, O2, and CO2 as the oxidants. Utilization of biomass by means of generating biogas is one of the easiest and cost effective methods of harnessing renewable energy. As India is an agricultural country, a tremendous amount of biomass and livestock waste is generated every year. Likewise the large population of India generates much food and municipal solid waste that is not being utilized for biogas generation. Fuel cells are one of the effective means of utilizing biogas, although the synthesis gas or hydrogen generated from biogas can also be used in internal combustion engines. Higher efficiency of fuel cells (45%) compared to internal combustion engines (30%) and even higher with co-generation systems (70%) make them highly desirable for biogas utilization for power generation. Investigations of hydrogen productionfor fuel cell use are in their infancy stage in India. Apart from a few scattered investigations not much work has been undertaken in the area of research. Large scale hydrogen production is achieved by steam reforming of hydrocarbons, in particular natural gas. Although the process is a proven technology it has come under considerable scrutiny due to its environmental impact and the energy intensive nature of the process. Several technical and scientific challenges have to be overcome for assimilation of the technology for hydrogen production from biogas and wide scale application in India. These challenges include development of less energy intensive features, highly active and poisons-resistant catalyst, and fuel cell development for utilization of biogas generated hydrogen. Hydrogen production from reforming of biogas: Review of technological advances and an Indian perspective. Available from: https://www.researchgate.net/publication/315896154_Hydrogen_production_from_reforming_of_biogas_Review_of_technological_advances_and_an_Indian_perspective [accessed Oct 16 2017].